2010
DOI: 10.1016/j.eururo.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Ipsilateral Recurrence After Nephron-sparing Surgery in Renal Cell Carcinoma

Abstract: RCC ipsilateral recurrence risk after NSS is significantly associated with tumour size >4cm, tumour bilaterality (synchronous or asynchronous), and PSM. Careful follow-up should be advised in patients presenting with such characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 28 publications
2
34
0
7
Order By: Relevance
“…Although currently debated, early studies of the clinical implications of positive margins demonstrated a higher risk of tumor recurrence and should be avoided in all cases. 25,26 Even when a positive margin never evolves into a clinically significant recurrence, the impact of rigorous surveillance may carry with it both a financial and emotion burden to the patient 27,28 The i-Cap scoring system can provide an essential tool not only to the pathologist but also to the treating urologist to aid in the creation of an appropriate post-operative care plan for the renal cell cancer patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although currently debated, early studies of the clinical implications of positive margins demonstrated a higher risk of tumor recurrence and should be avoided in all cases. 25,26 Even when a positive margin never evolves into a clinically significant recurrence, the impact of rigorous surveillance may carry with it both a financial and emotion burden to the patient 27,28 The i-Cap scoring system can provide an essential tool not only to the pathologist but also to the treating urologist to aid in the creation of an appropriate post-operative care plan for the renal cell cancer patient.…”
Section: Discussionmentioning
confidence: 99%
“…High-volume studies have not necessarily proved a clear correlation. 18,19 Nevertheless, some have demonstrated that PSM influences tumor recurrence rate, 20,21 but does not appear to have an effect on cancer-specific survival, 21 suggesting that conclusions should not be drawn without long-term follow-up. The prevalence of PSM in nephron-sparing techniques has been reported to be in the range of 4.9–8.1% for the open and laparoscopic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of R1 findings when the resection bed is grossly tumor-free has not been shown to have any significant effect on tumor-specific survival (19) (LoE 3). Patients with R1 findings are at increased risk of local recurrence (hazard ratio [HR] 11.5); note, however, that the data underlying this finding concerned a small group of patients (20) (LoE 3). If the definitive histopathological examination reveals R1 findings, then surveillance is indicated, rather than a second operation (21) (LoE 3, recommendation grade B).…”
Section: Resection Marginsmentioning
confidence: 59%